Agroecology and short marketing circuits: Approaches in Dialogue with Nature - Gómez Rodríguez, Dustin Tahisin; Barbosa Pérez, Ehyder Mario (Cooperativismo & Desarrollo, 2023)
The general objective of this paper is to describe the relationships that exist between agroecology and solidarity economy through the strategy called Short Commercialisation Circuits (SCC). The methodology is qualitative, and the method is a documentary review through matrices that seeks divergences and convergences of the authors. The main conclusion is that the strong sustainability developed by agroecology in dialogue with SCCs establishes spaces of resilience between socio-ecological systems, as well as the territorialities and territories where they are fertilised. These approaches reflect socio-ecological transitions that are in tune with the cycles of life. Precisely, the interactions with nature based on the wisdom of peasant, Afro-descendant or indigenous communities open up the possibility of a sustainable planet, as they have an impact on the geopolitical, economic, social, technological, and environmental spheres.
Keywords: agriculture; solidarity economy; rural economy; environment